2021
DOI: 10.3389/fphar.2021.668730
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Calcium Channels as Drug Target in Gastroesophageal Cancers

Abstract: Gastroesophageal cancers, including tumors occurring in esophagus and stomach, usually have poor prognosis and lack effective chemotherapeutic drugs for treatment. The association between dysregulated store-operated calcium entry (SOCE), a key intracellular Ca2+ signaling pathway and gastroesophageal cancers are emerging. This review summarizes the recent advances in understanding the contribution of SOCE-mediated intracellular Ca2+ signaling to gastroesophageal cancers. It assesses the pathophysiological role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 154 publications
(164 reference statements)
0
4
0
Order By: Relevance
“…To date, there are no drugs currently being used clinically that target the Ca 2+ signalling machinery, although several pharmaceutical companies are working on it. In order to develop new drugs, the molecular structures of the proteins involved must first be deciphered [ 86 ]. This is known under the term “basic research”.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no drugs currently being used clinically that target the Ca 2+ signalling machinery, although several pharmaceutical companies are working on it. In order to develop new drugs, the molecular structures of the proteins involved must first be deciphered [ 86 ]. This is known under the term “basic research”.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting SOCE-mediated Ca 2+ signaling in cancer cells is an emerging chemotherapy approach, and several SOCE blockers, including RP4010, are currently being evaluated in clinical trials [23]. As a second-generation TKI, afatinib received FDA approval to be used in targeted therapy for patients with EGFR mutation-positive cancers, but not for ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of SOCE tumor biology and cancer progression, it is plausible to suggest that the blockade of STIM1/Orai1-dependent Ca 2+ signaling can be a practical therapeutic approach for cervical cancer. Studies on preclinical animal models have demonstrated the potentials of several small-molecule SOCE inhibitors in cancer therapies [ 194 , 195 , 196 , 197 , 198 ]. However, these SOCE inhibitors have not been approved for clinical use for cancer therapies.…”
Section: Intracellular Ca 2+ Homeostasis and Store-operated Ca 2+ Entry (Soce)mentioning
confidence: 99%